Competence Of Female Journalists In Covering News Of The Indonesian Presidential Election 2024 On Antaranews.com - Musfialdy, Musfialdy; Kodarni, Kodarni; Soim, M (Indonesian Journal of Economics, Social, and Humanities, 2025)
The presidential election, which is one of the elections in Indonesia, is conducted through a direct election procedure. In the 2024 presidential election, there are many challenges and obstacles in carrying out journalistic duties. In the 2024 presidential election, journalists often put themselves in situations that occur during the coverage of news in the field. The high level of occupational danger in mass media and journalism in the coverage of the presidential election is considered an inappropriate job for women. The purpose of this study is to determine the competence of women journalists in covering news of the Indonesian presidential election of 2024 at Antaranews.com. Competency standards for journalists, based on Press Council Regulation Number: 1/ Regulation-DP/II/2010 on Journalist Competency Standards. In this study, researchers used 2 theories, namely muted group theory and social responsibility theory. The conclusion in this study is that female journalists in Antaranews are very competent in covering the Indonesian presidential election 2024. It is because female journalists have awareness, knowledge, and skills in covering the 2024 presidential election.